The application of nanofluids on three dimensional mixed convection heat transfer in equilateral triangular duct - Mohammed H.A.; Om N.I.; Shuaib N.H.; Hussein A.K.; Saidur R. (International Information and Engineering Technology Association, 2023)
In this work numerical predictions of mixed convective nanofluids flow and heat transfer in an equilateral triangular duct are reported. Three dimensional, laminar Navier-Stokes and energy equations were solved using the finite volume method. Pure water and four different types of nanofluids such as Ag, Au, Cu, diamond and SiO2 with volume fractions range of 1% ?; ? ?; 5% are used. This investigation covers Rayleigh number in the range of 1 104 ? Ra ? 1 106 and Reynolds number in the range of 100 ? Re ? 1000. The effects of different Rayleigh numbers, Reynolds numbers, nanofluid types, volume fractions of nanofluid, apex angles of the traingular duct, and radiation are investigated. The results presented in terms of streamlines, isotherms, Nusselt number, and pressure drop. The results revealed that the Nusselt number increases as Rayleigh number increases due to the buoyancy force effect. It is found that SiO2 nanofluid has the highest Nusselt number while Au nanofluid has the lowest Nusselt number among other nanofluids. The apex angle of the triangular duct has remarkable influence on the Nusselt number. An increasing of the duct apex angle decreases the Nusselt number value. The pressure drop increases as Reynolds number increases and apex angle decreases.